Review/N-glycans: The making of a varied toolbox. (October 2015) - Lannoo, Nausicaä; Van Damme, Els J.M.
Graphical abstract: Highlights: N -Glycan biogenesis takes place in different compartments of the secretory pathway. N -Glycans play important roles in protein folding, activity, and function. N -Glycan mutants display altered cell wall composition and stress responses. N -Glycans are involved in plant-pathogen interactions and development. Abstract: Asparagine ( N )-linked protein glycosylation is one of the most crucial, prevalent, and complex co- and post-translational protein modifications. It plays a pivotal role in protein folding, quality control, and endoplasmic reticulum (ER)-associated degradation (ERAD) as well as in protein sorting, protein function, and in signal transduction. Furthermore, glycosylation modulates many important biological processes including growth, development, morphogenesis, and stress signaling processes. As a consequence, aberrant or altered N -glycosylation is often associated with reduced fitness, diseases, and disorders. The initial steps of N -glycan synthesis at the cytosolic side of the ER membrane and in the lumen of the ER are highly conserved. In contrast, the final N -glycan processing in the Golgi apparatus is organism-specific giving rise to a wide variety of carbohydrate structures. Despite our vast knowledge on N -glycans in yeast and mammals, the modus operandi of N -glycan signaling in plants is still largely unknown. This review will elaborate on the N -glycosylation biosynthesis pathway in plants but will also critically assess how N -glycans are involved in different signaling cascades, either active during normal development or upon abiotic and biotic stresses.